Mimicry and relationships - Pryor, Kimberley Jane. (New York : Marshall Cavendish Benchmark, 2010)
"Discusses how animals use mimicry and relationships to protect themselves from predators or to catch prey"--Provided by publisher.
Includes index.
Keywords: Mimicry (Biology) -- Juvenile literature; Symbiosis -- Juvenile literature